Pengaruh Manajemen Latihan dan Motivasi terhadap Prestasi Akademik Anggota Paskibra di SMAN 12 Bandung Tahun Pelajaran 2023/2024 - Ananda Cipta Pamungkas (Journal on Education, 2024)
Implementation of education and training refers to a series of ongoing education management activities to achieve education and training goals effectively. The focus of this research is on Training Management and Motivation of Paskibra members at SMAN 12 Bandung to improve Academic Achievement. The aim of this research is to analyze the influence of Training Management and Motivation on the Academic Achievement of Paskibra Members at SMAN 12 Bandung. The method used is descriptive quantitative, data was collected through questionnaires distributed to fifty members of Paskibra SMAN 12 Bandung. Secondary data was obtained from literature related to problems and observations. Data analysis was carried out using Multiple Linear analysis. The research results show: 1) The Training Management variable (X1) significantly influences Academic Achievement (Y) with a t value of 2,893 and a significance of 0.006, indicating an influence of 12.8%. 2) The Motivation variable (X2) also significantly influences Academic Achievement (Y) with a t value of -2.666, a significance of 0.010, and an influence of 11.8%. 3) Simultaneously, Training Management and Motivation influence Academic Achievement (Y) with Fcount 4.228 and significance 0.020, showing an influence of 11.6%, while 88.4% is influenced by other variables not studied. Thus, this research concludes that training management and motivation have a positive impact on the academic achievement of Paskibra members at SMAN 12 Bandung